In Silico Study: Andrographolide Compounds and Their Derivatives as Antimalarials Targeted at PfENR - Auli , Winni Nur; Ramadhani, Syanindita Lulu; Firgianti, Sinta Rani; Sigalingging, Yonathan Adi Nugroho; Hasnaussalim, Hamidah; Yuliana , Rita; Saputri, Syabina Sofa (Prodi Kimia, 2025)
Malaria is an infectious disease that poses a significant danger due to its potential to cause severe anemia. The malaria parasite comes from the genus Plasmodium, which can attack erythrocytes. In recent years, good target proteins have been discovered as antimalarials. The target protein is taken from the type II fatty acid biosynthesis pathway, the fatty acid specific to Plasmodium falciparum is Enoyl Acyl Carrier Protein Reductase (PfENR). This study aims to evaluate the antimalarial activity of the Andrographolide compound which targets PfENR using in silico as an alternative for developing new drugs. Evaluation of the Andrographolide compound was carried out in silico with Autodock Tools and Biovia Discovery Studio Visualizer, then compared between the native ligand and the target compound, and the compound with the best interaction was determined so that it could provide a maximum therapeutic effect on the target compound. This research shows that the Andrographiside compound has a lower binding affinity, compared to native ligan is -5.94 kkal/mol and other compounds, namely -8.21 kkal/mol, so it has better bonding affinity, and the bond is reversible, making it suitable for developing new drugs. However, the Andrographiside compound still requires further molecular modifications to comply with Lipinski's rules.